PENGEMBANGAN TIKTOK UNTUK HASIL BELAJAR PADA SEL HEWAN DAN TUMBUHAN KELAS VIII SMP NEGERI 1 SIANTAR - Haloho, Egma Afli; Silalahi, Mastiur Verawaty; Silaban, Winarto (Smart Education, 2025)
Abstract: In order or by improve students' learning outcomes on animal as well as plant cell material in class VIII, this study intends to develop a science learning media based on the TikTok application. It also seeks to ascertain the viability of creating a video for TikTok-based in order to improve students learning outcomes on animal and plant cell material in class VIII. Finally, it seeks to ascertain how students react to the creation of TikTok- materials for improve students' learning outcomes on animal and plant cell material in class VIII. Low student learning results and a dearth of use of engaging, technology-based learning materials that are pertinent to students' digital habits form the basis of this study. The method used (R&D) with the ADDIE. The results of the study indicate TikTok-based learning media meets the feasibility criteria with a